2020
DOI: 10.1039/c9fo02026h
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the biological activities of selenium polysaccharides

Abstract: Selenium polysaccharides, an important organic selenium product, possess better antioxidant, antitumour, immune regulation, hypoglycaemic, and heavy metal removal activities than that of either polysaccharides or inorganic selenium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…Similar to the above results, many studies have demonstrated that selenium-polysaccharide exhibits the antioxidant activity in vitro [44][45][46][47]. The possible chemical mechanisms for the antioxidant activity were shown as follows: firstly, the hydroxyl groups in Se-ESPS-B1 and ESPS-B1 were reacted with ferric iron, which reduced the production of free radicals induced by ferric iron [48]. Secondly, selenium in Se-ESPS-B1 could also directly trap the electrophilic free radicals [49].…”
Section: Antioxidant Activity Assays Of Se-esps-b1supporting
confidence: 62%
“…Similar to the above results, many studies have demonstrated that selenium-polysaccharide exhibits the antioxidant activity in vitro [44][45][46][47]. The possible chemical mechanisms for the antioxidant activity were shown as follows: firstly, the hydroxyl groups in Se-ESPS-B1 and ESPS-B1 were reacted with ferric iron, which reduced the production of free radicals induced by ferric iron [48]. Secondly, selenium in Se-ESPS-B1 could also directly trap the electrophilic free radicals [49].…”
Section: Antioxidant Activity Assays Of Se-esps-b1supporting
confidence: 62%
“…Selenium is a trace element essential to many bacteria and animal species. [1,2,3,4] This essentiality is improved by biochemical connection between selenium and vitamin E. [5,6] There are multiple chemical forms of bioactive selenium, among which selenocysteine, the 21 st amino acid, has a prominent role. [7] Glutathione peroxidases (Gpx) are selenoenzymes responsible for scavenging peroxides and hydrogen peroxide at the expense of glutathione (GSH), preventing oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…HSI and VSI of sh were in uenced by 0.7mg/kg Nano-Se and 1% Nano-Se-enriched G. lemaneiformis, but not by 1% G. lemaneiformi. These indicate that dietary Nano-Se and Nano-Se-enriched G. lemaneiformis was better than dietary G. lemaneiformis in promoting immune function, since it is generally acknowledged that the immunity of the organism is related to the development of immune organs [13] . On the other hand, elevation of HSI re ected an increase in energy storage in grouper fed the dietary with Nano-Se or Nano-Se-enriched G. lemaneiformis [24], which is consistent with the result of weight gain in the same groups.…”
Section: Discussionmentioning
confidence: 90%
“…G. lemaneiformis is known with excellent Se enrichment ability [11]. Se can promote the activity of functional substances such as polysaccharides in G. lemaneiformis by modifying its structure [12,13]. It is feasible and effective to use proper G. lemaneiformis as feed ingredient for juvenile Paci c white shrimp [14].…”
Section: Introductionmentioning
confidence: 99%